Female professionals at work and home: a clash of priority - Rokis, Rohaiza (Institut Sosial Malaysia & Faculty of Human Ecology, UPM, 2009)
This article attempts to understand the experiences of female professionals at home and workplaces in Malaysia. The research setting is at PetCo”1. It applies three sociological methods that include participant observation, interview and questionnaires, which involved 259 questionnaire respondents and 34 interviewees. The study found that even though women workers enjoy their employment, they still consider family and home as the priority in life.